Counteracting constitutive activity of Orai1 with an H171Y mutation - Marko, Ricarda (Jihočeská univerzita, 2022)
The functions and structures of the Orai1-ANSGA mutation are still not completely known. To further investigate possible changes in pore structure, Orai1 ANSGA and H171Y in combination with different amino acids were used in cysteine-crosslinking studies, to see if the ANSGA and H171Y mutations affect the orientation of pore-lining residues.
Counteracting constitutive activity of Orai1 with an H171Y mutation
Keywords: Ion channels; Ca2+ channels; Orai1; ANSGA; cysteine-crosslinking; H171Y